(untitled) (Research, Society and Development, 2022)
Cryopreservation of oocytes and embryos is a supplementary technique for in vivo and in vitro embryo production. In the last decade, the technique has been improved but did not achieve a satisfactory commercial level. Also, the results were variable. The pregnancy and live birth rates were 16 to 52% and 5.3 to 26.9% after implantation of vitrified embryos, respectively (from the year 1993 to 2020). In final consideration, the quality of oocytes and embryos is the most important factor to obtain better results after cryopreservation. The addition of antioxidant and lipid-depleting agents to the medium is a factor that improves cryogenic tolerance. Additionally, two-step vitrification is a reliable method for cryopreservation. Studying epigenetic effects and introducing lipidomic, transcriptomic and proteomic technologies can help improve this technology.